NEONATAL SEPSIS: CAUSATIVE BACTERIA AND THEIR RESISTANCE TO ANTIBIOTICS - Muhammad, Zardad; Ahmed, Ashfaq; Hayat, Umar; Wazir, Muhammad Salim; ullah, Rafiyat; Waqas, Huma (Journal of Ayub Medical College Abbottabad, 2010)
Background: Neonatal sepsis is one of the major causes of neonatal morbidity and mortality, particularly in developing countries. The objective of this study was to determine the causative bacteria and level of their resistance to commonly used antibiotics. Methods: This descriptive study was carried out at Ayub Teaching Hospital, Abbottabad from April 2009 to January 2010. All neonates of either gender admitted in neonatology unit with clinical sepsis and positive blood culture were included in the study. Neonatal period was defined as 28 days of life at term and up to 44 weeks of gestational age in preterm babies. One hundred and thirty neonates of either gender were studied during the period. Blood sample for culture was taken from a peripheral vein or an artery ensuring standard anti-septic measures. BACTEC technique was used for obtaining bacterial growth and drug sensitivity after incubation of 24-48 hours. Second blood culture was also performed in few cases which were not showing improvement after initial treatment. Results: Male to female ratio was 1.3:1. Early and late onset sepsis was found in 29.2% and 70.8% respectively. Gram-negative bacteria were more frequent than grampositive bacteria with a frequency of 54.6% and 45.4% respectively. Gram-positive and gram-negative bacteria showed high resistance against commonly used antibiotics such as ampicillin, amoxicillin, cefotaxime, ceftriazone and gentamicin. Conclusion: Staph. aureus is the most common gram-positive bacterium and E. coli is the most common gram-negative bacterium causing neonatal sepsis. Grampositive and gram-negative bacteria are highly resistant against commonly used antibiotics such as ampicillin, amoxicillin, cefotaxime, ceftriazone and gentamicin, and are relatively more sensitive to less commonly used drugs like amikacin and ceftazidime. Keywords: Neonatal sepsis, antibacterial resistance, gram-positive, gram-negative